Jesus and the Last Supper - Pitre, Brant James (Wm. B. Eerdmans Publishing Co, 2015)
Preface -- Abbreviations -- 1. The Problem of the Last Supper -- Jesus and Judaism -- The Self--Understanding of Jesus -- The Eschatology of Jesus -- Jesus and the Early Church -- Method of Proceeding -- 2. The New Moses -- The New Moses in Early Judaism -- The Feeding of the Multitude -- The Blood of the Covenant -- The New Bread of the Presence -- 3. The New Manna -- The Manna in Early Judaism -- The Lord's Prayer and the Eschatological Manna -- The Teaching in the Synagogue at Capernaum -- 4. The Date of the Last Supper -- The Apparent Contradiction -- The Essene Hypothesis -- The Johannine Hypothesis -- The Synoptic Hypothesis -- The Passover Hypothesis -- 5. The New Passover -- The Passover in Early Judaism -- The Temple Context of the Last Supper -- The Body and Blood of the Lamb -- 6. The Eucharistic Kingdom of God -- The Messianic Banquet in Early Judaism -- Eating and Drinking with Abraham, Isaac, and Jacob -- Jesus' Vow at the Last Supper -- 7. Conclusion -- Bibliography -- Index of Authors -- Index of Subjects -- Index of Biblical and Other Ancient Literature